"We refused to work until we had better means for handling the bodies". Discipline at the Australian Graves Detachment*. Issue 1 (2nd January 2018) - Fathi, Romain
Abstract: The Australian Graves Detachment, a unit over 11 hundred men, was formed in March 1919 on the Western Front. Its mission was to exhume and re-bury the war dead in a small area of Northern France where the Australian Imperial Force had fought. While war memorialization and grief are significant fields of research in First World War studies, much remains to be written with regard to the processes of burying the millions of dead. Little, for example, has been written about the men who undertook the daunting tasks of exhuming and burying. This article seeks to contribute to this emerging area of inquiry by exploring how discipline was enforced at the Australian Graves Detachment through a range of strategies such as negotiation and care for both the men's physical and mental wellbeing. It argues that at a time where inflexible military discipline and justice were difficult to enforce, such non-coercive forms of control proved more effective for disciplining the men than formal military sanctions. This article first examines the nature of the work undertaken by the Australian Graves Detachment. Second, it turns to the disciplinary issues which arose from the ranks. Third, the article analyses the strategies put in place by the Commanding Officer of the Detachment to maintain discipline within the unit. In particular, the article highlights how entertainment played a key role in maintaining discipline and morale within the detachment, providing the men with a wide variety of amusing activities that kept them under their officers' watch and control. Sports, games, theatre, movies, the camera club, afternoon teas and other forms of entertainment insured that men had as little idle time as possible. Entertainment became the cornerstone of the Commanding Officer's attempts to limit misconduct, and to ensure that the unit would complete its mission.